EXPLORING THE MULTIFACETED DIMENSIONS OF LINGUISTIC PERSONALITY: A COMPREHENSIVE ANALYSIS - Abdumalikova Zebiniso (Social science and innovation, 2023)
This article delves into the intricate facets of linguistic personality within the realm of contemporary linguistics. It navigates through the attempts to comprehend the concept of "linguistic personality," examining its structure, and classifying its models. Rooted in the paradigm of anthropocentrism, the study underscores the indispensability of language in understanding the human experience. Linguoculturology emerges as a promising field, with "linguistic personality" at its core. The article explores various linguistic personality models, considering linguistic, linguoculturological, and communicative aspects. It discusses the interplay of language, culture, and ethnicity, presenting a synthesis of linguistic personalities across diverse individuals within a language